(untitled) (Latakia University Journal - Arts and Humanities Sciences Series, 2019)
يحاول البحث قراءة النص الطلليّ للكشف عن صورة الذات الإنسانيّة فيه، وعلاقتها بالمكان/الطلل من خلال التركيز على الصراع بين ثنائية الذات والطلل مع الطبيعة من جهة، وصراعها مع الزمن من جهة أخرى، للوصول بعدها إلى معرفة طرق الذات في تجاوز محنتها في الطلل. في سبيل ذلك يدرس البحث عدداً من النصوص الطلليّة دراسة تحليلية نصيّة، لا تلتزم منهجاً محدداً، بل تهتدي بإضاءات من مناهج الدرس الأدبي المتعددة، أملاً في الوصول إلى تفسير دقيق للنصوص المختارة، وتحقيق الهدف المنشود من البحث. This research aims to study The Pre-Islamic poem, in order to examine the image of the human self in it, and to know its relation to the by concentrating at the struggle between the twines: self and runes against nature first one, and against time secondly, in order to know the self methods to avoid its problem in runes . This research studies some texts as a textual analysis which isn’t restricted to a specific critical approach. It employs different literary approaches due to the researcher’s aim to produce an accurate interpretation, as well as, a sound reading of the texts, hoping to introduce a correct explanation for the texts in order to chive the research’s aim.